(untitled) (Journal of Economic Research & Business Administration, 2020)
The current research continues the series of studies aimed to analyze the issues in regards to bank efficiency in the Baltic banking market. The goal of the current paper is to empirically test the Quiet Life Hypothesis (QLH) and to investigate the relationship between market concentration and efficiency in the banking sector of Latvia, Lithuania and Estonia. Two QLH-related hypotheses are stated for the research purposes. To achieve the established goal, the authors run a multiple regression analysis, using efficiency of an individual bank as a dependent variable. In turn, independent variables include market concentration proxied by Herfindahl-Hirschman Index (HHI) and bank-specific measures, such as market share, profitability and productivity. Efficiency scores for individual banks were estimated applying Data Envelopment Analysis (DEA). Study is based on the sample data of 33 banks operating in the Baltic countries, covering the period of 2007-2013 (227 observations). Data processing was made with application of DEAFrontier and SPSS software. In the result of the performed analysis the stated hypotheses are rejected. Thus, there is no empirical evidence that market power, and consequently, market concentration in the Baltic banking sector negatively impacts the efficiency of individual banks. At the same time, researchers should pay special attention to two conceptual issues in the process of developing methods for regulating Bank liquidity: the size of the Bank’s equity capital and the conditions of the external environment.